Boosting the separation of bulk charge in Na0.5Bi0.5TiO3 by the synergetic effect of ferroelectric polarization and thin-sheet shape. Issue 19 (1st October 2021) - Ji, Jiamin; Pu, Yongping; Chang, Liangliang; Ouyang, Tao; Wang, Peifeng; He, Chenpu; Zhou, Shiyu
Abstract: Bulk charge recombination is one of the main blocks to the photocatalytic efficiency. The internal electric field brought by ferroelectric polarization in ferroelectric materials and the decreasing transport distance of carriers by tailoring morphology have been proposed to overcome this problem. Herein, thin-sheet Na0.5 Bi0.5 TiO3 photocatalyst with strong ferroelectric polarization was prepared by topochemical molten salt synthetic (TMSS) method. Without co-catalysts, thin-sheet Na0.5 Bi0.5 TiO3 represented excellent photocatalytic performance that degradation efficiency towards RhB, tetracycline and ciprofloxacin were 99.8%, 76.6% and 68.3% under simulated sunlight within 100 min, respectively. P - E loops and XPS measurement demonstrated that thin-sheet shape led to a large number of atoms missing on the surface, resulting in lattice distortion, and the spontaneous polarization was greatly improved at the same time. The synergetic effect of strong ferroelectric polarization and thin-sheet shape of Na0.5 Bi0.5 TiO3 promoted the separation of photo-generated carriers in the bulk. This work proved that single ferroelectric materials possessed glorious ability for photocatalytic reaction via minishing the thickness and enhancing the degree of distortion to build strong internal electric field.